Diversity of macrofungi in UiTM Negeri Sembilan Forest / Ummi Masyitah Abdul Razak - Abdul Razak, Ummi Masyitah (2016)
Macrofungi is a type of fungi that can be seen with unaided eye and it plays an important role in the ecosystem. However, the study and information about the macrofungi diversity is not well updated and documented in Malaysia. A study on the diversity of macrofungi was carried out at UiTM Negeri Sembilan Forest. Macrofungi samples were collected from three different areas within UiTM Negeri Sembilan forest. The macro morphology of the macrofungi has been recorded in situ and samples were collected for identification purposes. A total of 23 species of macrofungi belonging to six orders under phylum Basidiomycota and Ascomycota has been identified during the samplings. The order Polyporales had the highest number of species (13), followed by unidentified species (4), Agaricales (2), Hymenochaetales (1), Boletales (1), Russulales (1) and Pezizales (1). The Shannon- Wiener index and Pielou- index for the macrofungi diversity in the UiTM Negeri Sembilan Forest were 1.757 and 0.560 respectively. In conclusion, there is need of continuous research to be done in order to get better knowledge about the diversity of macrofungi particularly in Malaysia.